An Environmental Impact Analysis Of Ecogastronomy In Bangli Regency, Bali - Bondan Pambudi; I Made Darsana (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
The impact of the COVID-19 pandemic is in the past, and it is evident that the environmental impacts of tourism, especially in inner areas with fragile ecosystems, are even more intense, especially in tourism metropolitan areas like the Bangli Regency, which is characterised by highlands, farming systems, and protected areas. This work attempts to explore and describe the impacts of the development of ecogastronomy in Bangli Regency, concentrating on the management and impacts of natural resources, pollution and waste, ecosystems and wildlife, and climate change. The researchers utilised a qualitative case study with in-depth interviews, constructivist observation, document review, and thematic analysis using NVivo. For the climate change impacts analysis, the researchers employed ISM as a qualitative paradigm. The study found that while awareness and conservation from overexploitation of resources and pollution are constructive, many risks are associated with the disturbance of the ecosystem. ISM emphasised natural resource management and climate change as two primary systemic elements that override the ecosystem. It was found that the development of ecogastronomy has the potential to promote environmental sustainability, especially with coordinated integrated environmental management, and that eco-gastronomy is an inner tourism.